2019
DOI: 10.1111/myc.13004
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic value of a nested polymerase chain reaction for diagnosing cutaneous sporotrichosis from paraffin‐embedded skin tissue

Abstract: Summary Background The gold standard for diagnosis of cutaneous sporotrichosis involves the isolation of the fungus, Sporothrix, by a culture test. Generally, the sampling for the culture test is performed at the same time as skin biopsy under local anaesthesia. However, the culture test may occasionally return a false negative result. Objective The aim of our study was to investigate the diagnostic value of a molecular method for diagnosing cutaneous sporotrichosis from formalin‐fixed and paraffin‐embedded (F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…Sensitivity and specificity of PCR were as high as 100% and 98.7%, respectively. 13 In our case, histopathological review from cat wound (demonstrated yeast-like organism), history of cat contact and location of cat's wound which developed on its nose brought us recognition of mycoses that grew at subcutaneous level. Sporothrix schenckii was detected from PCR performing.…”
Section: Discussionmentioning
confidence: 72%
“…Sensitivity and specificity of PCR were as high as 100% and 98.7%, respectively. 13 In our case, histopathological review from cat wound (demonstrated yeast-like organism), history of cat contact and location of cat's wound which developed on its nose brought us recognition of mycoses that grew at subcutaneous level. Sporothrix schenckii was detected from PCR performing.…”
Section: Discussionmentioning
confidence: 72%
“…In this work, the nested PCR methodology performed was similar to that described by Hu et al (40) based on amplification of the 18S region of ribosomal RNA (ITS), using specific primers for Sporothrix sp.. A semi-nested PCR methodology was developed for the diagnosis of human sporotrichosis in tissues embedded in paraffin with high sensitivity and specificity, but few cases were analyzed and there was a lack of details that make its reproducibility difficult (49). Also, the authors used the same chemical DNA extraction kit but it was not reported how the paraffin blocks were sectioned (49). Hu et al (40) described a nested PCR assay for the detection of S. schenckii…”
Section: Discussionmentioning
confidence: 99%
“…A semi-nested PCR methodology was developed for the diagnosis of human sporotrichosis in tissues embedded in paraffin with high sensitivity and specificity, but few cases were analyzed and there was a lack of details that make its reproducibility difficult ( 49 ). Also, the authors used the same chemical DNA extraction kit but it was not reported how the paraffin blocks were sectioned ( 49 ). Hu et al ( 40 ) described a nested PCR assay for the detection of S. schenckii for diagnosing cutaneous sporotrichosis in frozen skin tissues ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations